2008
DOI: 10.1016/j.socscimed.2007.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differentials in parental health seeking for childhood illness in Vietnam

Abstract: Vietnam's sustained investment in primary healthcare since the onset of socialism has lowered infant and childhood mortality rates and improved life expectancy, exceeding progress achieved in other poor countries with comparable levels of income per capita. The recent introduction of user fees for primary healthcare services has generated concern that economic policies may have adversely affected health-seeking behavior and health outcomes of the poor, particularly among impoverished families who are members o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 13 publications
3
34
0
1
Order By: Relevance
“…The inequity displayed in care seeking could be explained by a multitude of factors, one being the cost of seeking care, as has been shown in studies from around the world [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The inequity displayed in care seeking could be explained by a multitude of factors, one being the cost of seeking care, as has been shown in studies from around the world [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that ethnic minorities in Vietnam live in the more remote and isolated areas [26,27] and that there are larger concentrations of poverty in rural areas [28]. Therefore, to further come to terms with possible confounding stratification according to socioeconomic factors was made.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have speculated upon the nature of disparities in health care practices among ethnic minorities and majorities in Vietnam (Trinh, Dibley, and Byles 2007;Sepehri et al 2008;Teerawichitchainan and Phillips 2008;Do 2009;Målqvist et al 2011). These studies, consisting largely of local case studies or regional analyses, have found that ethnic minority pregnant women tend to enter prenatal care at later gestation ages, have fewer pregnancy check-ups, lack adequate vaccinations, prefer home delivery, and rely upon traditional birth attendants during delivery.…”
Section: Study Context: Ethnicity and Ethnic Disparities In Vietnammentioning
confidence: 99%
“…The control variables included in our models are measures of the characteristics of individuals, as well as the households and communities within which they reside as suggested in the previous studies on prenatal care utilization and ethnic disparities in Vietnam (Trinh, Dibley, and Byles 2007;Sepehri et al 2008;Teerawichitchainan and Phillips 2008;Do 2009;Teerawichitchainan and Amin 2010;Målqvist et al 2011;Tran et al 2011). These variables, presented in Table 1, include women's age, birth parity, occupation, and household wealth quintile.…”
Section: Measurementsmentioning
confidence: 99%